Cholera toxin inhibits human hepatocarcinoma cell proliferation in vitro via suppressing ATX/LPA axis - Xia Qi; Deng An-mei; Wu Shan-shan; Zheng Min (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the antitumor effect of cholera toxin (CT) in hepatocellular carcinoma (HCC) in vitro and the mechanisms underlying the effect. Methods: Human hepatocellular carcinoma cell lines Hep3B and Huh7, which expressed moderate and high level of autotaxin (ATX), respectively, were used. Cytokine level in the cells was evaluated using ELISA assay, and cell proliferation was investigated using MTT assay. ATX expression was determined using Western blot. ATX/lyso-PLD activity in the conditioned medium was measured using FS-3, a fluorescent lysophosphatidylcholine (LPC) analogue, as substrate. Results: Exposure to CT (7.5 and 10 ng/mL) significantly inhibited the cell growth, decreased secretion of proinflammatory cytokine TNF-α and promoted secretion of anti-inflammatory cytokines IL-4 and IL-10. CT at 10 ng/mL markedly suppressed ATX expression in Hep3B and Huh7 cells. Furthermore, ATX and lysophosphatidic acid (LPA) were found to be crucial for growth of the cancer cells. CT could inhibit TNF-α-induced expression and secretion of ATX that led to decreased activity of lysophospholipase D, thus decreasing the conversion of LPC to LPA. Conclusion: CT inhibits hepatocellular carcinoma cell growth in vitro via regulating the ATX-LPA pathway.